2011
DOI: 10.1111/j.1470-6431.2010.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

Usage of dishwashers: observation of consumer habits in the domestic environment

Abstract: Over the years, appliance manufacturers have been successful in developing dishwashers that enable consumers to save time, energy and water very conveniently. Within the last 20 years the savings in energy consumption exceed 30%, and the average water consumption per cycle has been more than halved. As a result, it is very hard for the majority of people to compete with the efficiency of a dishwasher when dishes are done by hand. However, consumer habits (e.g. regarding the use of the dishwasher load capacity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 1 publication
0
20
0
1
Order By: Relevance
“…One of the daily activities in every household is washing the dishes. Even in households with dishwashers, a couple of items are still washed by hand (Richter, , ). A variety of techniques exist which are used for manual dishwashing.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…One of the daily activities in every household is washing the dishes. Even in households with dishwashers, a couple of items are still washed by hand (Richter, , ). A variety of techniques exist which are used for manual dishwashing.…”
Section: Introduction and Theoretical Backgroundmentioning
confidence: 99%
“…Looking at the other 56.2%, so those who do own an eco‐programme, just 12.4% of them said they use it always and 37.8% use it often—which means half of the owners don't use it often. Earlier studies also showed low values: Richter () measured 17.0% usage frequency for the eco‐programme, Stamminger and Streichardt () 17.7%. This shows the need of increasing the usage of the resource saving eco‐programme.…”
Section: Introductionmentioning
confidence: 92%
“…Hairdryers (8) 137 (8) 142 (8) 27. Airing 101 (20) 81 (17) 120 (22) 28. Floor heating (comfort) 77 (4) 76 (3) 76 (3) Clothes care 1 Note that if multiple devices are used at the same time in a household, these are still entered for the same variable, which represents a certain device/activity and a certain hour of the day.…”
Section: Personal Hygienementioning
confidence: 99%
“…However, few studies have linked energy-related behaviour with direct measurements of energy use. There are examples of studies that have combined measurements and diaries with a focus on a few activities, such as dishwashing habits [20] or lighting patterns and presence in offices [21]. There are also examples of smaller studies where hot water usage as well as electricity usage in households have been studied together with diaries in order to identify usage and load patterns visually [22,23].…”
Section: Introductionmentioning
confidence: 99%